Strategi Belajar Siswa Berprestasi pada Mata Pelajaran Pendidikan Agama Kristen Kelas XII di SMAN 2 Palangka Raya - Rahmelia, Silvia; Supardi, Jeffry; Rania (Institut Agama Kristen Negeri Toraja, 2025)
This study aims to describe the learning strategies of high-achieving students in the Christian Religious Education subject for grade XII at SMAN 2 Palangka Raya. The research employed a qualitative approach, with data collection techniques including questionnaires, in-depth interviews with seven high-achieving students, literature studies, and documentation. The results revealed that the students’ learning strategies encompass: (1) creating structured study schedules, (2) periodic repetition of challenging material, (3) active reading using highlighting and concise note-taking techniques, and (4) efforts to maintain concentration through managing their learning environment. These strategies align with the concept of Self-Regulated Learning (SRL), which emphasizes planning, self-evaluation, and commitment to achieving academic goals. The findings offer practical implications for teachers in facilitating students to develop independent learning strategies and serve as a reference for students to enhance academic achievement through SRL and self efficacy.Penelitian ini mengungkap strategi belajar mandiri siswa berprestasi pada mata pelajaran Pendidikan Agama Kristen (PAK) kelas XII di SMAN 2 Palangka Raya. Melalui pendekatan kualitatif dengan teknik pengumpulan data angket, wawancara mendalam terhadap tujuh siswa berprestasi, studi kepustakaan, dan dokumentasi, ditemukan strategi belajar siswa berprestasi meliputi: (1) pembuatan jadwal belajar terstruktur, (2) pengulangan materi sulit secara berkala, (3) membaca aktif dengan teknik highlight dan catatan ringkas, serta (4) upaya menjaga konsentrasi melalui pengelolaan lingkungan belajar. Strategi ini sejalan dengan konsep Self-Regulated Learning (SRL) yang menekankan perencanaan, evaluasi diri, dan komitmen untuk mencapai tujuan akademik. Temuan ini mengkonfirmasi relevansi SRL dalam konteks PAK, sehingga guru dapat mengembangkan strategi belajar mandiri. Disamping itu penelitian ini dapat menjadi referensi bagi siswa untuk meningkatkan prestasi belajar melalui strategi belajar yang mengintegrasikan SRL dan self efficacy.